ANALISIS KESIAPAN GURU DALAM MENGIDENTIFIKASI KARAKTERISTIK DAN MENGEMBANGKAN POTENSI ANAK CERDAS BERBAKAT DI KELAS IV UPTD SD NEGERI FOLANGKAI - Belandina Edelweis Atalo; Asriyanti Karim; Amos Kalung; Yessy Mata; Petrus Mau Tellu Dony (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze teacher readiness in identifying the characteristics and developing the potential of gifted and talented children in fourth-grade students at the Folangkai Elementary School Technical Implementation Unit (UPTD), located in Wolwal Tengah Village, Alor Barat Daya District, Alor Regency. A common problem in elementary schools is teachers' lack of understanding in analyzing the characteristics of gifted and talented children, resulting in their potential not being optimally developed. This study used a qualitative approach with a case study method. Data collection techniques were conducted through observation, interviews, and documentation of fourth-grade teachers, as well as analysis of the learning outcomes and activities of gifted and talented children. The results indicate that teachers already have a basic understanding of the characteristics of gifted and talented children, such as outstanding academic ability and speed in understanding material. However, teachers still experience difficulties in systematically identifying them due to limited research and practical guidance. Furthermore, efforts to develop the potential of gifted and talented children are still limited to providing additional assignments, the lack of additional learning programs, and the lack of structured and challenging learning programs tailored to their needs. This study recommends ongoing training for teachers and the development of differentiated learning programs to support the optimal development of gifted and talented children at the UPTD of Folangkai Elementary School. Keywords: Teacher readiness, gifted and intelligent children, identification of characteristics, potential development, elementary school.